The Ideology of Teak Root Craftsmen in Cabak Blora Village in Facing Global Competition - Gunadi Gunadi (International Conference on Science, Education, and Technology, 2021)
This study aims to reveal how the underlying ideology of craftsmen in the creation of teak root craft art in Cabak Blora village is facing global competition. In particular, this research aims to 1) explain the ideology of craftsmen in the creation of teak root crafts in the village of Cabak Blora, 2) explain the types and forms of development of teak root crafts in the village of Cabak-Blora, 3) explain the maintenance strategy carried out by craftsmen in the face of global competition. This study used a qualitative approach. This research was conducted in Cabak Village, Jiken District, Blora Regency. The subjects of this research were the “Gembol Karya” teak root home craftsmen and the “Akar Seni” collective craftsman community. The data collection methods used were observation, interviews, and documentation. The data was analyzed qualitatively using interactive model analysis techniques consisting of several stages, namely data collection, data reduction, data presentation, and conclusions/verification. The results showed that the ideology of the collective craftsmen was more open in developing creativity and home craftsmen were only oriented as craftsmen who carry out the orders of their owners. The types of works produced between the two communities were different, home crafters were more oriented towards abstract furniture and decorations, while collective craftsmen prefer realistic teak root sculptures, both of which used a rustic-style approach. The maintenance strategy carried out by collective artisans was that the inheritance was more open to the public, while home craftsmen were more focused on the family sphere. All craftsmen should be able to synergize with each other so that the art of teak root crafts in Blora Regency continues to be sustainable and developed.